Beyond topography: addressing the functional impact of social skills training for students with autism. Issue 2 (2nd April 2020) - Sabey, Christian; Ross, Scott; Goodman, Jordan
ABSTRACT: Students with autism spectrum disorder often require social supports to function well in a mainstream class setting. Researchers have demonstrated the effects of social skills training for students with autism, but their work has focused primarily on topographically defined outcomes, such as increasing the frequency of social behaviours. More research is needed to address the functional impact of social skills training on social experiences, such as improvements in the quality of life for students with autism. This study examined the effects of a behavioural skills training form of social skills intervention on the social interactions of students with autism in an inclusive school setting. The intervention increased participants' social behaviour. However, its mixed results in the quality of peer responses may be a more meaningful indicator of its effect on the quality of social lives of the participants. The authors discuss the implications of these findings for current practice and future research.